O método design thinking como instrumento de sustentabilidade urbana. Uma proposta aplicada para a questão do descarte irregular de resíduos na cidade de Uberlândia, MG, Brasil. - Leticia Del Grossi Michelotto; Fernando Luiz Araujo Sobrinho (Confins)
Over the last twenty years, urbanization rates in Brazil have increased significantly. According to IBGE (Brazilian Institute of Geography and Statistics), most of the Brazilian population, 84.72%, live in urban areas and a little more than half of the Brazilian population (56.5% or 117.2 million inhabitants) lives in only 5.6% of the cities, which are those with more than 100 thousand inhabitants. The Greater Region with the highest percentage of urban population is the Southeast, with 93.14% of people living in urban areas. This urban expansion has caused environmental problems, mobility issues (transit, transportation, access) and socio-spatial segregation. Brazilian urban policy for medium and large cities is based on a model of dispersion guided by public policies and property speculation. This model impacts negatively both population and the environment, especially with deforestation of native areas for the incorporation of new urban areas. The aim of this work is to propose innovative solutions for urban planning using the theory of the design thinking method with the proposal to minimize impacts in the search for an ideal of urban sustainability. Design thinking corresponds to a set of methods and processes to address problems related to future information acquisition, knowledge analysis and solutions proposals. The study will take as a case study the city of Uberlândia, an important middle-sized city, located in the state of Minas Gerais, southeastern Brazil.